The voices of teachers: reasons for choosing the teaching profession, underlying values - María Amelia Pidello; Beatriz Rossi; María de los Ángeles Sagaztizabal (Pontificia Universidad Católica del Perú, 2013)
This paper analyzes, from the views expressed by teachers in activity, the motivations that led and lead them to uphold the performance of the teaching task. This problem is systematically surveyed in the framework of the project Observatory of the conceptions of teachers and future teachers about the school, teacher training and students (Irice/Conicet, OIE/Unesco). The comprehension of the senses and meanings that guide the choice of teaching implied, by the subjects questioned, a reflection on the constitutive aspects of the teaching role and a travel through the spaces of confluence of processes and representations. This study allowed us to recognize the prevailing needs in such choice of career, as well as the understanding of its significance and the values that guide it.